2023
DOI: 10.1093/carcin/bgad030
|View full text |Cite
|
Sign up to set email alerts
|

Mutational signatures and increased retrotransposon insertions in xeroderma pigmentosum variant skin tumors

Abstract: Xeroderma pigmentosum variant (XP-V) is an autosomal recessive disease with an increased risk of developing cutaneous neoplasms in sunlight-exposed regions. These cells are deficient in the translesion synthesis DNA polymerase eta, responsible for bypassing different types of DNA lesions. From the exome sequencing of eleven skin tumors of a genetic XP-V patients’ cluster, classical mutational signatures related to sunlight exposure, such as C>T transitions targeted to pyrimidine dimers, were identified.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although the NER mechanism is the primary DNA repair pathway in UV exposure‐related damage, studies show that NER is also essential in repairing environmental chemical‐induced DNA damage such as smoking, chemotherapeutics, and aflatoxins 7 . Molecular studies in various tumors in XP patients showed that signature mutations associated with environmental factors, like smoking and aflatoxin exposure, were prominently expressed 8 …”
Section: Introductionmentioning
confidence: 99%
“…Although the NER mechanism is the primary DNA repair pathway in UV exposure‐related damage, studies show that NER is also essential in repairing environmental chemical‐induced DNA damage such as smoking, chemotherapeutics, and aflatoxins 7 . Molecular studies in various tumors in XP patients showed that signature mutations associated with environmental factors, like smoking and aflatoxin exposure, were prominently expressed 8 …”
Section: Introductionmentioning
confidence: 99%